INTERAKSI ANTARA BAHAN KEMASAN DAN LAMA PENYIMPANAN PRODUK SALEP ANTIMASTITIS TERHADAP DAYA HAMBAT PERTUMBUHAN BAKTERI - Zalizar, Lili (Jurnal Gamma, 2011)
Lili ZalizarStaf Pengajar Jurusan Produksi Ternak, Fakultas Pertanian-Peternakan, Universitas Muhammadiyah MalangAlamat Korespondensi : Puncak Buring Indah B6-51 MalangEmail: lilizalizarthahir@yahoo.comABSTRACTThe study aimed to understand the interaction between packaging materials and storage timeantimastitis ointment products against bacterial growth inhibition was performed at the Departmentof Animal Husbandry Malang Muhammadiyah University is using an ointment made from a mixtureof betel leaf and Meniran. The bacteria used in testing this ointment is Staphylococcusaureus.Experiment using completely randomized design with factorial pattern (3x4) with 3 (three)replications. The first factor is packaging material consisting of three (3) treatment of plastic bottles,glass and cans as well as the second factor is differences in storage duration of 2, 4, 6 and 8 weeks.Variable that measured the inhibition of bacterial growth herbal ointment. Result of the researchshowed that antimastitis ointment in plastic packaging, glass and cans until day 56 still can inhibitbacterial growth. Inhibition of growth of the smallest bacteria contained in the ointment storedwithin the packaging made from tin.Key words: packaging material,storage duration, bacterial growth inhibition